METHODOLOGY OF TEACHING LATIN AND FOREIGN LANGUAGES IN CREDITS TRANSFER SYSTEM AT MEDICAL HIGHER EDUTATIONAL INSTITUTIONS OF UKRAINE - Гуцол, М.І. (World of Medicine and Biology, 2017)
The article analyzes the aspects of the teaching methodology of foreign and Latin languages, in higher medical educational institutions. They relate to such important questions: 1) why do the learner of foreign and Latin languages will use them; 2) what do you need to learn to use foreign language effectively; 3) what do you need to learn to use the Latin language effectively; 4) the competence of a person; how do they serve to study foreign and Latin languages. The aim is to develop and implement (on the basis of scientifically substantiated recommendations) the optimal methods and methods of organizing the process of studying foreign and Latin languages, including on the basis of an adaptive learning system.
Keywords: innovative teaching methods; educational process; intensification; verification of knowledge; competencies; recommendations